Graduate of Riga Polytechnic Institute, Engineer, Inventor and Athlete Arno Līcis - Lanka, Ērika; Zigmunde, Alīda (History of Engineering Sciences and Institutions of Higher Education, 2019)
The article summarizes the career of a graduate of the Faculty of Mechanics (1964) of Riga Polytechnic Institute Arno Līcis. The article reveals and describes his work while being an engineer at the Riga Electromachine Building Factory (RER), at the Latvian Scientific Research Institute of Trauma- tology and Orthopaedics (LSRITO) and in the printing house «Jāņa sēta», as well as being an inventor. It has been discovered that he had promoted orienteering sports and had significant achievements in competitions of various scale, inclu- ding mass competition named «Magnēts» managed by him, which had been taking place since 1969. This is the first research on the life and professional activities of engineer A. Līcis, which is dedicated to his 80th birthday to be ce- lebrated in July 2019. Data from the personal archive of A. Līcis, documents of the Latvian State Historical Archives and the collection of the National Library of Latvia are collected in this article.